Gambaran pelaksanaan swamedikasi dan pendapat konsumen apotek mengenai konseling obat tanpa resep di wilayah Bantul - Susan Fitria Candradewi; Susi Ari Kristina (Universitas Ahmad Dahlan, 2017)
The use of non-prescription drugs of self-medication has been done by the community to treat various conditions of ailments. The drugs which are often used in self-medication generally belong to the class of non-prescription drugs. One of the things which influence people's self-medication is the information about drugs which is easy to be accessed. The concept development of pharmacy services means that pharmacists are in charge of patients in quality of service improvement, so that the pharmacists have a duty to give proper information related to the use of non-prescription drugs. This research aims to determine consumers' opinion regarding counseling of non-prescription drugs and the overview of non-prescription drugs implementation in Bantul. This research is a descriptive research with direct survey method by using questionnaires and observation sheets. The sampling is done by using purposive sampling technique. The result of this research shows that there are three classes of the most widely purchased in the implementation of self-medication which are antipyretic analgesics (28%), supplements/vitamins (19%), and the last is cough, cold and flu drugs (15%). Most consumer already know drugs usage rules, and it is showed by the number of 71%, and pharmacists become factor in considering drug selection is showed by the number of 34%, while 96% consumers claim to read drug's label at first purchase. Consumers' opinion in counseling is that they most require counseling of non-prescription drugs, which is showed by the number of 89%, while 75% of consumers had been getting counseling of non-prescription drugs with duration of 1 to 5 minutes. The conclusion of this research is the overview of self-medication implementation of non-prescription drugs in Bantul shows that the most purchased of non-prescription drugs is analgesic antipyretic. Implementation of counseling non prescription drugs in Bantul shows that most (89%) of the consumers need counseling from pharmacist, as many as 75 % consumers get non prescription drug counseling from pharmacist, and the average time of non prescription drug counseling was 5 minute.